Optimization in science and engineering in honor of the 60th birthday of Panos M. Pardalos - Rassias, Themistocles M. 1951-; Floudas, Christodoulos A. 1959-; Butenko, Sergiy 1977- (Springer, 2014)
Comprises a collection of contributions from experts in diverse aspects of optimization Includes introductory surveys and in-depth technical papers Covers a wide variety of topics that interest researchers, students and practitioners in Mathematics, Operations Research, Computer Science, Industrial and Systems Engineering